The use of pyridine derivatives as accelerators in the solvent extraction of nickel from a nitrate matrix by LIX®63/Versatic™10 - Hutton-Ashkenny, M.; Barnard, K.; Ibana, Don (Elsevier, 2015)
Direct solvent extraction (DSX) for the purification of nickel and cobalt from laterite leach liquors is an attractive alternative to precipitation of an intermediate product. With commercialisation of the Direct Nickel nitric acid leaching process, application of this technology to high magnesium bearing nitrate liquors has become of interest. The combination of the hydroxyoxime LIX®63 and the carboxylic acid Versatic™10 results in synergistic extraction of nickel and cobalt and can selectively remove these metals from calcium and magnesium. Nickel stripping, however, is particularly slow. Previously, the accelerator tributylphosphate has been used to increase the rate of nickel stripping. Unfortunately, a high concentration is required which detrimentally increases the required pH for nickel extraction. Pyridine derivatives combined with Versatic 10 also result in synergistic extraction of nickel and cobalt with reasonable stripping rates, although at higher extraction pH and with poorer separation from calcium. The combination of the three reagents (LIX 63, Versatic 10, and a pyridine derivative) was therefore investigated to determine if high metal separation and reasonable nickel stripping rates could be achieved in the same system. Nonyl-4-pyridine carboxylate at lower concentrations than required with tributylphosphate resulted in faster nickel stripping and extraction when using LIX 63/Versatic 10 without impacting nickel extraction pH. A statistical experimental design was subsequently used to model the effects of the reagent concentrations in the tertiary system on nickel and cobalt extraction and to determine optimum reagent concentrations.